Social Stigma and Resilience of Banjarmasin Correctional Centre Clients - Nur Syifa; Gladis Corinna Marsha; Dyta Setiawati Hariyono (Fakultas Ushuluddin, Adab dan Dakwah - Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The purpose of this study was to determine the effect of social stigma on the resilience of Banjarmasin Class 1 Correctional Centre clients. The researcher used a quantitative correlational research method. Respondents in this study were 100 people selected using a purposive sampling technique, with the criterion that clients had undergone mandatory reporting at the Bapas for approximately 1 week to 4 months. The research instrument used the Connor-Davidson Resilience Scale (CD-RISC-25) and the Perceived Social Stigmatisation Scale (STS). The research data were analysed using simple linear regression in JASP 0.18.3. The analysis showed no effect of social stigma on resilience (t = 3.88, p = 0.89), thereby rejecting the hypothesis. This finding indicates that although Bapas clients still face social stigma, this condition does not directly weaken the client's ability to recover, adapt, and maintain healthy psychological functioning. The implications of this research contribute to social psychology studies, providing insight into the dynamics of resilience during social transition. Social stigma does not always function as a risk factor that weakens resilience. The presence of social stigma will only affect individuals if they interpret it negatively.